Comparison of Intravenous Morphine with Sublingual Buprenorphine in Management of Postoperative Pain after Closed Reduction Orthopedic Surgery - Soltani, Ghasem (Arch Bone Jt Surg, 2015)
BACKGROUND: Postoperative pain is a common side effect following surgery that can significantly reduce surgical quality and patient’s satisfaction. Treatment options are morphine and buprenorphine. We aimed to compare the efficacy of a single dose of intravenous morphine with sublingual buprenorphine in postoperative pain control following closed reduction surgery. METHODS: This triple blind clinical trial was conducted on 90 patients referred for closed reduction orthopedic surgery. They were older than 18 years and in classes I and II of the American Society of Anesthesiologists (ASA) with an operation time of 30-90 minutes. Patients were divided into two groups of buprenorphine (4.5µg/kg sublingually) and morphine (0.2mg/kg intravenously). Baseline characteristics, vital signs, pain score, level of sedation and pharmacological side effects were recorded in the recovery room (at 0 and 30 minutes), and in the ward (at 3, 6 and 12 hours). SPSS version 19 software was used for data analysis and the significance level was set at P<0.05. RESULTS: Ninety patients were studied, 60 males and 30 females with a mean age of 37.7±16.2 years. There was no significant difference between the two groups in terms of baseline characteristics. Pain score in the morphine group was significantly higher than the buprenorphine group with an average score of 2.5 (P<0.001). Postoperative mean heart rate in the buprenorphine group was four beats lower than the morphine group (P<0.001). Also, in the buprenorphine 48.6% and in the morphine group 86.7% of cases were conscious in recovery (P=0.001) with a higher rate of pruritus in the latter group (P=0.001). CONCLUSION: Sublingual buprenorphine administration before anesthesia induction in closed reduction surgery can lead to better postoperative pain control in comparison to intravenous morphine. Due to simple usage and longer postoperative sedation, sublingual buprenorphine is recommended as a suitable drug in closed reduction surgery.